A feasibility study on the RxBox - Cacnio, Paolo Gabriel C.; Castro, Jeselle Y.; Crisostomo, Karen Marian L.; Santos, Rhio Alleli D.
The objective of this study is to find out whether RxBox, a telemedicine device which offers an integrated medical solution, is a feasible undertaking. It should enable remote medical diagnosis and testing, while offering a built in healthcare information system. The study is divided into four parts where the different factors and measures were considered to assess the feasibility of the device. The first part allowed the group to characterize the need for such device and how this need would be addressed through the product's capabilities. From this, the potential customers of RxBox were identified together with the sales and growth projections. Strategies were also streamlined to reach the identified markets of the product. The succeeding part delved into the specific requirements to operate an organization which would offer RxBox. This encompasses activities during the implementation and start-up phases of the project This also included looking at suppliers for the necessary resources to create an RxBox. The next part, which is probably the most crucial among the parts, was performed to determine how much is needed to fund the project and to see if the project is profitable and sustainable as compared to the companies within the same industries. Given that funding is obtained, the business would have good returns that would make the initial investment worth it. The last part involved evaluation of the social-economic contributions of the project apart from its financial profitability. Overall, the RxBox project was found to be feasible in all parts.